Edukasi Bullying dan Bahaya Penggunaan Gadget Melalui Program Smart pada Remaja - Sri Rezeki; Erin Padilla Siregar; Amelia Erawaty Siregar (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2024)
Cyberbullying is an action intended to embarrass, intimidate, spread ugliness and hatred in cyber media. One of the cyber media is social media ask.fm. Cyberbullying often occurs in teenagers, this can affect the emotions of teenagers who are still quite unstable in controlling their emotions. In this research, the problem formulated is whether there is an influence of cyberbullying on social media ask.fm on the emotional development of teenagers. The aim of this research is to determine the effect of cyberbullying on ask.fm social media on adolescent emotional disorders. The research method used is a survey research method using a questionnaire as a data collection instrument. The catharsis theory used in this research states that catharsis is a clearing of emotional conflict within oneself through talking about it and the deindividuation theory states that there is a feeling of loss of personal identity and the emergence of anonymity in the group. The anonymous feature on ask.fm social media provides opportunities for perpetrators to carry out cyberbullying on ask.fm. The sample in this study was 30 students, who had been victims and perpetrators of cyberbullying. Hypothesis testing shows Tcount ≥ Ttable (3.049 ≥ 1.660) so that H0 is rejected and Ha is accepted, so this means that these two variables have a significant influence. This research showed that teenagers dared to carry out attacks only through the social media ask.fm, with anonymous facilities that made it easy for the perpetrators to express all their frustration without their identities being known. And as victims, teenagers generally reject it by responding emotionally.